Reasons for choosing Russia as the main direction of labor migration from Tajikistan in the context of COVID-19 pandemic and sanctions - A. Kh. Rakhmonov (Управление)
The article examines the impact of the currency crisis and the consequences of COVID-19 pandemic on labor migration from Tajikistan to Russia, the impact of new anti-Russian sanctions by the European Union and United States of America on Tajik labor migrants, as well as the repulsive factors of the reorientation of migrants from Tajikistan to a new direction of labor emigration to the Organization for Economic Co-operation and Development (OECD) countries and the Persian Gulf. Russia is the main migration channel for labor migrants from Tajikistan. During the entire period of their stay in Russia they face various crisis phenomena in the country along with the local population. Each crisis in Russia has had a different negative impact on the situation of Tajik labor migrants. During the currency crisis in 2014–2015, Tajik migrants lost their income by twice due to the fall in the Russian ruble exchange rate. During the COVID-19 period, because of the introduction of a self-isolation regime in Russia, since the end of March 2020, the Russian labor market has been compressed, many Tajik labor migrants have lost their jobs. The new anti-Russian sanctions have already affected Tajikistan. Due to the European and the United States sanctions against Russia, the total flow of labor migration from Tajikistan to Russia has decreased. The aim of the article is to identify the attractive factors of the orientation of Tajik migrants to labor emigration to Russia and the repulsive factors of the reorientation of Tajik migrants to a new direction of labor emigration to the OECD and Persian Gulf countries.